A phase II RCT and economic analysis of three exercise delivery methods in men with prostate cancer on androgen deprivation therapy - Alibhai, Shabbir M; Santa Mina, Daniel; Ritvo, Paul; Sabiston, Catherine; Krahn, Murray; Tomlinson, George; Matthew, Andrew; Segal, Roanne; Warde, Padraig; Durbano, Sara; O’Neill, Meagan; Culos-Reed, Nicole (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background Androgen deprivation therapy is commonly used to treat prostate cancer, the most common visceral cancer in men. However, various side effects often worsen physical functioning and reduce well-being among men on this treatment. Based on existing evidence, both resistance and aerobic training provide benefits for this population yet adherence rates are often low. The method of exercise delivery (supervised in-center or home-based) may be important, yet few studies have compared different models. Additionally, long-term exercise adherence is critical to achieve sustained benefits but long-term adherence data and predictors of adherence are lacking. The primary aim of this phase II, non-inferiority randomized controlled trial is to determine whether three exercise training delivery models are equivalent in terms of benefits in quality of life and physical fitness in this population. Secondary aims include examination of long-term adherence and cost-effectiveness. Design Men diagnosed with prostate cancer, starting or continuing on androgen deprivation therapy for at least 6 months, fluent in English, and living close to one of two experienced Canadian study centers are eligible. Participants complete five assessments over one year, including a fitness assessment and self-report questionnaires. Socio-demographic and clinical data collection occur at baseline, bone mineral density testing at two time points, and blood work is performed at three time points. Participants are randomized in a 1:1:1 fashion to supervised personal training, supervised group training, or home-based smartphone- and health coach-supported training. Each participant receives a detailed exercise manual, including illustrations of exercises and safety precautions. Participants are asked to complete 4 to 5 exercise sessions per week, incorporating aerobic, resistance and flexibility training. Participant intensity levels will be monitored. The intervention duration is 6 months, with 6 months additional follow-up. Outcomes include: body composition, fitness testing, quality of life and fatigue, biological outcomes, and program adherence. Cost information will be obtained using patient diary-based self-report. Discussion The goals of this study are to gain a better understanding of health benefits and costs associated with commonly used yet currently not compared exercise delivery models as well as an increased understanding of adherence to exercise. Trial registration The trial has been registered at clinicaltrials.gov (Registration # NCT02046837 ), registered January 20th, 2014.